Optimasi Pengendalian Banjir melalui Pemodelan Numerik 1D (Studi Kasus: Kanal Banjir Timur Semarang) - Rachmadi, Afif; Joubert, Marasi Deon; Budi, Agung Setya; Harianto, Harianto (JURNAL TEKNIK HIDRAULIK, 2025)
The Eastern Flood Canal of Semarang is a flood control system with a total length of 14.6 km, receiving inflows from Kali Gede through the operational gates of Pucang Gading Dam, Kali Kedung Mundu, Kali Bajak, and Kali Candi, before discharging into the Java Sea. On March 13, 2024, flooding occurred in Semarang due to operational constraints, channel blockages caused by waste accumulation, and reduced channel capacity due to material buildup along the banks, exacerbated by extreme rainfall exceeding 150 mm/day and high tides. This study aims to assess channel capacity and improve operational decision-making for the Pucang Gading Dam to enhance flood control performance and ensure community safety. Hydraulic simulations were performed using HEC-RAS version 6.2, incorporating upstream flood hydrographs and downstream tidal boundary conditions from Tanjung Mas Port. The study yielded a peak discharge of 608 m3/s, a channel capacity with freeboard of 365 m3/s (equivalent to Q25), and a maximum channel capacity discharge of 526 m3/s. Overflow was observed in all scenarios analyzed, with overflow depths ranging from 5 to 40 cm . To optimize the operation of the Pucang Gading Dam, it is crucial to regulate  inflow to the Eastern Flood Canal while accounting for lateral inflows from tributaries. Additionally, raising parapets by approximately 15–40 cm in strategic locations and preventing material accumulation along the channel banks is recommended. This study demonstrates the effectiveness of HEC-RAS in assessing channel capacity and formulating practical flood mitigation strategies.